Potential Analysis and Development Strategy of Kampoeng Hidroponik As A Village Youth Entrepreneurship Pioneer - Ajeng Setyoningrum, Indri; Indah Cahyani, Atika; Gusmanti, Reza (Universitas Negeri Padang, 2022)
Kampoeng Hidroponik of Sobontoro Village is a social innovation developed by village youth called Rupa Desa group. This attempt is an initiation to improve the conditions of slum settlements in their environment. Kampoeng Hidroponik of Sobontoro Village is a form of community empowerment that is carried out through social entrepreneurship. This study aims to analyze the business potential of Kampoeng Hidroponik of Sobontoro Village as a pioneer of social entrepreneurship by village youth. This study used qualitative research by describing the internal and external environmental conditions through the PEST factor. Then analyzed by SWOT analysis to formulate the development strategy of Kampoeng Hidroponik. Data collection technique using observation, interview and literature review. The research results show the developmental strategies for the enhancement of product management such as: (1) product differentiation for customer choice; (2) develop hydroponic vegetable processed products; (3) create customer loyalty programs; (4) marketing to upper middle-class customers such as restaurant and hotel; (5) join the hydroponics and business community to disseminate information; (6) strengthen promotional content on social media. Meanwhile, in term of strengthening community empowering, development strategies include: (1) increasing the capacity and competence of Rupa Desa members as facilitator and managers of educational tourism; (2) create a visit and training program for students, university, and homemakers group; (3) increase urban farming campaign; and (4) socialize and educate the surrounding community who have not joined yet